Support and coping strategies used by chronic renal patients undergoing hemodialysis (Research, Society and Development, 2020)
This study aims to demonstrate the coping strategies used by chronic renal patients undergoing hemodialysis. This is a field research, of an applied, descriptive and exploratory nature, with a qualitative approach, carried out in a nephrology clinic, located in the municipality of Floriano - Piauí. The production of data based on Bardin's Content Analysis technique (2011) was interpreted. It is noteworthy that the entire research was carried out in accordance with the Guidelines and Norms of research with human beings and guided by the ethical principles of the Resolution of the National Health Council (CNS) No. 466/2012. The findings were categorized into two thematic axes: Category 1: Family support and Category 2: Use of religion / beliefs. It is revealed that family support represents to the patient an essential tool in the physical, social and emotional adaptation in relation to the hemodialysis treatment. It is emphasized that religion represents strength, comfort, relief, support and optimism in coping with chronic renal failure, and it is evident that despite the difficulties faced during hemodialysis, patients develop strategies to face and live with the disease, directly implying your quality of life.